Spatial Multimodal analysis (SMA) - Mass Spectrometry Imaging (MSI) - Bjärterot, Patrik; Nilsson, Anna; Shariatgorji, Reza; Andrén, Per (Uppsala University, 2023)
The files above are MALDI-MSI (Matrix Assisted Laser Desorption Ionization - Mass Spectrometry Imaging) experiments. The dataset contains both imzML, which is the common MSI open file type, and csv, containing x, y positions in tissue as well as m/z and intensity, which is a more user friendly format. A major difference between the two types is that the imzML contains raw data, whereas the csv data is peak-picked, explaining the discrepancy in file sizes. The data contained in this dataset should be enough to recreate the MSI parts of the manuscript.

The purpose of the experiments was to demonstrate that MALDI-MSI and ST (Spatial Transcriptomics) could be done on the same tissue. MALDI-MSI was done first, and ST second, so there is no expected difference in the tissue compared to a regular MALDI-MSI run, however, the experiments where ST was run subsequent to MALDI-MSI required non-conductive glass which is not the standard in the MSI- field. To compare, experiments done on the commonly used conductive (ITO) glass slides are also contained in this dataset

For any questions about the dataset or to request access to any files not uploaded here, please contact per.andren@farmbio.uu.se
Keywords: Medical biotechnology not elsewhere classified; Medical and Health Sciences; Medicin och hälsovetenskap; Pharmaceutical and Medical Biotechnology; Läkemedel- och medicinsk processbioteknik